Effect of Vitamin A, Zinc and multivitamin supplementation on the nutritional status and retinol serum values in school-age children (2018)
Micronutrient deficiency or “Hidden Hunger” represents the most widespread form of malnutrition in the world. The aim of this study was to evaluate the effect of supplementation with Vitamin A as a single dose, Zinc and Vitamin A + Zinc on nutritional status, and on serum retinol and zinc levels in schoolchildren. A database total of 80 schoolchildren (girls = 47 and boys = 33) were evaluated about the effect of supplementation with vitamin A (VA), Zinc (Zn) and VA + Zn on nutritional anthropometric status, and on serum retinol and zinc values. Serum retinol concentrations were determined by HPLC, according to Bieri method, considering <20 μg/dL Vitamin A deficiency (DVA), 20–30 μg/dL DVA risk (RDVA) and >30 μg/dL normal VA; serum zinc was analyzed by Flame Atomic Absorption Spectrometry, considering ≥0.72 μg/dL normal zinc and <0.72 μg/dL zinc deficiency (DZn). Data were analyzed using SAS program Statgraphics XVI, and a significant p < 0.05 was considered. The deficiency of the nutritional consumption of zinc was high in the students, contrary to the consumption of vitamin A which was normal. The observed prevalence of DVA was 6.25%, RDVA 23.75% and DZn 97.50%. The isolated or combined supplementation of vitamin A and Zinc contributes to the maintenance of the anthropometric state; however, they are ineffective in the cases of low consumption of these nutrients to reach optimum circulating values.